Kinetic Study on Catalytic Cracking of Rubber Seed (Hevea brasiliensis) Oil to Liquid Fuels - Wara Dyah Pita Rengga; Prima Astuti Handayani; Sri Kadarwati; Agung Feinnudin (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
Reaction kinetics of catalytic cracking of rubber seed oil to liquid fuels has been investigated. The reac-tion was performed with sulfuric acid as catalyst at temperatures of 350-450 oC and the ratio of oil-catalyst of 0-2 wt.% for 30-90 minutes. Kinetics was studied using the model of 6-lump parameters. The parameters were rubber seed oil, gasoline, kerosene, diesel, gas, and coke. Analysis of experimen-tal data using regression models to obtain reaction rate constants. Activation energies and pre-exponential factors were then calculated based on the Arrhenius equation. The simulation result illus-trated that the six-lump kinetic model can well predict the product yields of rubber seed oil catalytic cracking. The product has high selectivity for gasoline fraction as liquid fuel and the smallest amount of coke. The constant indicates that secondary reactions occurred in diesel products compared to gaso-line and kerosene. The predicted results indicate that catalytic cracking of rubber seed oil had better be conducted at 450 oC for 90 minutes using 0.5 wt.% catalyst. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)